The Scoop on SCOBY (Symbiotic Culture of Bacteria and Yeast): Exploring Consumer Behaviours towards a Novel Ice Cream - Mehta A; Serventi L; Kumar L; Torrico DD (MDPI (Basel, Switzerland), 2023)
With the growing demand for sustainable practises, the food industry is increasingly adopting circular economy approaches. One example is recycling the symbiotic culture of bacteria and yeast (SCOBY) used in kombucha fermentation to create value-added products. However, consumer acceptance of such novel products remains unclear. To address this, the present study examined consumer attitudes towards ice cream made with SCOBY as an ingredient and how this affected their intention to consume it. Drawing on the theory of planned behaviour (TPB) and additional constructs such as emotions and food neophobia, an online survey was conducted with New Zealand consumers (N = 170). Results showed that the TPB constructs significantly predicted the intention to consume SCOBY ice cream. Moreover, by adding emotions to the constructs, the model's explanatory power was enhanced. Attitudes, subjective norms, and emotions were the main predictors of intention, which in turn was found to be the main predictor of behaviour. Participants' beliefs about the safety and taste of SCOBY ice cream were significantly correlated with their intention and behaviour, as were the opinions of nutritionists/dietitians, friends, and family. The model accounted for 21.7% of the variance in behaviour and 57.4% of the variance in intention. These findings can be used to plan marketing strategies related to waste-to-value-added products such as SCOBY ice cream.
Keywords: SCOBY; consumer research; emotions; food neophobia; sensory evaluation; theory of planned behaviour (TPB)